The Implementation of PhET Simulation Media to Improve Junior High School Students' Understanding of Heat and Heat Transfer Concepts - Ainaya Risna Augustine; Syafrizal Idris; Nanda Novita; Halimatus Sakdiah; Deassy Siska; Nurul Fajri Saminan (SAINTIS Publishing, 2025)
This study aims to determine the effect of using PhET (Physics Education Technology) simulation media on enhancing students’ conceptual understanding of heat and heat transfer at SMP Negeri 1 Cot Girek. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group type. The sampling technique used was purposive sampling, involving a total of 50 students Class VII A as the experimental group and Class VII B as the control group, each consisting of 25 students. The instrument used was a multiple-choice test administered as both a pretest and a posttest to measure students' conceptual understanding. The results showed that the average posttest score in the experimental class was 71.4, while in the control class it was only 52.8. Hypothesis testing using an independent sample t-test on the posttest data revealed a significance value of 0.001 ( 0.05), indicating a significant difference between the two classes after the treatment. Meanwhile, the N-gain scores showed an improvement of 71% (high category) in the experimental class and 54% (medium category) in the control class. Thus, it can be concluded that the use of PhET simulation media is effective in improving students’ conceptual understanding of heat and heat transfer, especially in schools with limited laboratory facilities.